Unsupervised person re‐identification based on adaptive information supplementation and foreground enhancement - Wang, Qiang; Huang, Zhihong; Fan, Huijie; Fu, Shengpeng; Tang, Yandong (IET image processing, 2024)
Unsupervised person re‐identification has attracted vital interest because of its ability to protect privacy, significantly lower the expense of manual annotation, and eliminate the need for data labels. General unsupervised methods train the network only through global features, which causes the fine‐grained information contained in local features to be ignored in the recognition process, resulting in large amounts of label noise and affecting the recognition accuracy. Moreover, more robust pedestrian features can also improve the accuracy of clustering and enable unsupervised person re‐identification to obtain better results. To address these issues, first, a dual‐branch structure was proposed, which separately obtains the global features of the pedestrian and the local features by dividing the global features into a few equal sections. Then, an adaptive information supplementation (AIS) method based on the k‐nearest neighbor algorithm is designed to ascertain each local feature's relevance to the global features, calculating adaptive weight scores for information supplementation. Finally, these weight scores are used to reallocate the weights of the global features in each part, acquiring features that contain more pedestrian information during the representation learning process. These better features are used to reduce label noise to obtain more accurate pseudo‐labels. Second, an adaptive foreground enhancement module (AFEM) was proposed and inserted before clustering to increase the robustness of pedestrian features, which increases the precision of the pseudo‐labels that are produced after clustering. Experiments on Market‐1501, DukeMTMC‐reID, and MSMT17 demonstrate that the proposed method achieves better results than state‐of‐the‐art methods in fully unsupervised person re‐identification tasks. We design an adaptive foreground enhancement module (AFEM), which can adaptively enhance the foreground pedestrian features of the input features, obtain more discriminative features, enhance the clustering effect and more accurate pseudo labels. We propose an adaptive information supplement (AIS) method that can adaptively supplement global features with finer‐grained local information to obtain features that are better suited for person re‐identification and effectively reduce the noise of pseudo‐labels.